2017
DOI: 10.1007/s40804-017-0089-8
|View full text |Cite
|
Sign up to set email alerts
|

The Culture Variable Vis-à-Vis Anti-bribery Law: A Grey Area in Transnational Corporate Criminal Liability

Abstract: Cross-border transactions are generating corresponding globalisation of law enforcement efforts. Culture has significantly influenced the legal analysis of anti-bribery law. With the increase of transnational bribery, benefits from globalisation will be undermined unless an effective legal regime can mitigate the harm of bribery. It is perceived that corruption in China is more prevalent than in the West given its embedded place in Chinese culture. It is further alleged that Chinese multinational companies (MN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Although some societies aspire to good relations between business and religion, this situation rarely obtains (Pavarala & Malik, 2010). The present study provides evidence that the reality is far more complicated, as Bu (2018) suggests. While religion can be used to promote a positive business reputation in Indonesia, this study reveals that strong religious beliefs can hide unethical decision-making, as suggested in previous studies (Hunt & Vitell, 1993).…”
Section: Discussionsupporting
confidence: 61%
“…Although some societies aspire to good relations between business and religion, this situation rarely obtains (Pavarala & Malik, 2010). The present study provides evidence that the reality is far more complicated, as Bu (2018) suggests. While religion can be used to promote a positive business reputation in Indonesia, this study reveals that strong religious beliefs can hide unethical decision-making, as suggested in previous studies (Hunt & Vitell, 1993).…”
Section: Discussionsupporting
confidence: 61%
“…The ‘Eight Amendment to the Criminal Law’ is similar to initiatives implemented in recent decades in the West, including the FCPA (Yin et al., 2011). But it is largely symbolic (Bu, 2018). Enforcing this anti‐corruption law would underscore the seriousness of Beijing’s drive to uproot corruption both domestically and internationally and counter the popular narrative that ‘corruption is China’s friend’.…”
Section: Discussionmentioning
confidence: 99%
“…The criticism is although an affordable gift or hospitality is unlikely to be penalised, it is difficult to quantify the same because of the obscure line between a legitimate expenditure and an unlawful bribe (Bu, 2018). Thus, the UK's Serious Fraud Office (SFO) would only prosecute upon evidence of systematic bribery rather than a one-off payment (Bu, 2018). The post-legislative scrutiny report on the UKBA acknowledged that the UKBA is silent on CH.…”
Section: Ukmentioning
confidence: 99%
“…Questions arise as to what constitutes 'normal' expenditure within a given sector, what is the meaning of "reasonable and proportionate hospitality", and what are the "standards of norms applying in a particular sector"(Select Committee on the Bribery Act 2010, 2019). There is no ceiling stated in the UKBA for expenses in gifts and hospitality (Bu, 2018). Table 2 below succinctly states the UK's position on corruption and CH.…”
Section: Ukmentioning
confidence: 99%
See 1 more Smart Citation